Pengaruh Problem Solving Skill dalam Model Pembelajaran Project Based Learning terhadap Hasil Belajar Siswa Sekolah Menengah Kejuruan - Zulfannur Zulfannur; Lilik Anifah; I Gusti Putu Asto Buditjahjanto (Universitas Cokroaminoto Palopo, 2024)
One of the challenges in education is the deficiency in critical thinking and problem-solving skills, which can be attributed to the limited implementation of approaches that foster problem-solving. This study seeks to determine whether problem-solving skills within the Project-Based Learning (PBL) model affect students' learning outcomes at SMKN Sugihwaras in light vehicle engineering. The primary aim is to investigate the impact of problem-solving skills, fostered through the PBL model, on the learning outcomes of these students. The research adopts a predictive quantitative approach to foresee the influence of problem-solving skills within the PBL framework on student learning outcomes. Data collection methods include observations and student test results, while data analysis is conducted using simple linear regression. This statistical method assesses the effect of a single independent variable on a dependent variable. The simple linear regression analysis results reveal an R-squared value of 0.6063. This indicates that 61% of the variance in learning outcomes (y_score) can be explained by problem-solving skills (x_score), with the remaining 39% attributed to factors outside the model. Consequently, the study concludes that the null hypothesis (H0) is rejected, and the alternative hypothesis (H1) is accepted, demonstrating a significant impact of problem-solving skills within the PBL model on the learning outcomes of class XI students at SMKN Sugihwaras.